In silico investigation of propofol binding sites in human serum albumin using explicit and implicit solvation models. (October 2017) - Shityakov, Sergey; Roewer, Norbert; Förster, Carola; Broscheit, Jens-Albert
Graphical abstract: Abstract: All-atom molecular dynamics (MD) simulations are presented on general anesthetic propofol bound to human serum albumin (HSA) due to the drug pharmacokinetics and pharmacodynamics in the circulatory system. We implemented the explicit and implicit solvation models to compare the binding affinity of propofol at the different binding sites (PR1 and PR2) in the HSA protein. Only the implicit solvation models provided the evidence in accordance with the experimental data indicating that the HSA-ligand interactions are dominanted by hydrophobic forces due to the higher drug affinity at the PR1 position with a ΔGMM-PB/SA value of −23.44 kcal mol −1 . Overall, this study provides important information on the accuracy of explicit and implicit solvation models to characterize the propofol interaction with different HSA binding sites.